The effectiveness of marketing communication element used by Ikhlas Consultant & Services (ICS), Johor Bahru to build brand equity / Siti Nurbadriah Shafie - Shafie, Siti Nurbadriah (2011)
There are many brand names of products and services emerge in the market today, but to sustain and survive in the industry it quite difficult. It is difficult to create brand equity and attract customer awareness towards company products and services. Thus, this study is done to examine what are the effective marketing communication elements that can be practiced by Ikhlas Consultant & Services to build brand equity. The data for this study is sourced from questionnaires distributed to 80 respondents around Skudai, Johor. There are two types of assisted questionnaires designed, which are multiple choice, and likert scale. All data were analyzed using frequency analysis and cross tabulation. The result indicated the effective marketing communication that can be used by Ikhlas Consultant & Services in order to increase customer awareness and create customer loyalty. Recommendations to Ikhlas Consultant & Services to build Takaful Ikhlas Brand Equity more prefer to marketing communication tools that can be practiced by Ikhlas Consultant & Services.